Studi Eksperimen Aktivitas Fotografi untuk Menurunkan Tingkat Kecemasan dan Stres - Edwin Adrianta Surijah; Ni Kadek Julian Dian Wahyuni; Misael Mahendras Bokoua Labulu; Listiyani Dewi Hartika (Fakultas Psikologi Universitas Pancasila, 2018)
Camera feature on a smartphone may bring positive impacts but it was rarely scientifically investigated. This research examines therapeutic effect of photography in reducing anxiety and stress symptoms through experimental design. Twenty participants were enrolled into two studies and were split into control group and treatment group receiving twelve sessions of photography therapy. Anxiety and stress were measured with DASS-42. Wilcoxon signed rank test and binary logistic regression showed photography therapy sessions were associated with lower level of anxiety and stress on both study groups. Careful conclusion of therapeutic photography efficacy was discussed due to low level of control during experiment.